2023
DOI: 10.1080/10872981.2023.2176734
|View full text |Cite
|
Sign up to set email alerts
|

How information literacy influences creative skills among medical students? The mediating role of lifelong learning

Abstract: This research investigated the influence of information literacy on the creative skills of medical students through the mediation of lifelong learning. A cross-sectional survey was conducted for data collection among medical students, recruited through a stratified convenient sampling procedure, of Khyber Pakhtunkhwa, Pakistan. The questionnaire was personally administered by visiting each college with written permission. A total of 473 survey responses were collected and analysed using the partial least squar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
0
0
Order By: Relevance
“…This study demonstrates that information literacy has a significant impact on the lifelong learning of medical students. Findings align with previous research, indicating that information literacy helps students acquire and process information and enhances their problem-solving and innovative capabilities (Naveed et al, 2023). Furthermore, Tachie-Donkor and Ezema (2023) observed that medical students' preference for internet resources positively correlates with their information-seeking behaviors and lifelong learning.…”
Section: Information Literacysupporting
confidence: 86%
“…This study demonstrates that information literacy has a significant impact on the lifelong learning of medical students. Findings align with previous research, indicating that information literacy helps students acquire and process information and enhances their problem-solving and innovative capabilities (Naveed et al, 2023). Furthermore, Tachie-Donkor and Ezema (2023) observed that medical students' preference for internet resources positively correlates with their information-seeking behaviors and lifelong learning.…”
Section: Information Literacysupporting
confidence: 86%